What Is the Correct Answer about The Dress’ Colors? Investigating the Relation between Optimism, Previous Experience, and Answerability - Karlsson, Bodil S. A.; Allwood, Carl Martin (Frontiers in Psychology, 2016)
The Dress photograph, first displayed on the internet in 2015, revealed stunning individual differences in color perception. The aim of this study was to investigate if lay-persons believed that the question about The Dress colors was answerable. Past research has found that optimism is related to judgments of how answerable knowledge questions with controversial answers are (Karlsson, Allwood & Buratti, 2016). Furthermore, familiarity with a question can create a feeling of knowing the answer (Reder & Ritter, 1992). Building on these findings, 186 participants saw the photo of The Dress and were asked about the correct answer to the question about The Dress’ colors (“blue and black”, “white and gold”, “other, namely…” or “there is no correct answer”). Choice of the alternative “there is no correct answer” was interpreted as believing the question was not answerable. This answer was chosen more often by optimists and by people who reported they had not seen The Dress before. We also found that among participants who had seen The Dress photo before, 19 %, perceived The Dress as “white and gold” but believed that the correct answer was “blue and black”. This, in analogy to previous findings about non-believed memories (Scoboria & Pascal, 2016), shows that people sometimes do not believe the colors they have perceived are correct. Our results suggest that individual differences related to optimism and previous experience may contribute to if the judgment of the individual perception of a photograph is enough to serve as a decision basis for valid conclusions about colors. Further research about color judgments under ambiguous circumstances could benefit from separating individual perceptual experience from beliefs about the correct answer to the color question. Including the option “there is no correct answer” may also be beneficial.